Effect on levels of dietary protein and cassava on performance and body composition of chickens - Phuah, C. H.; Hutagalung, R. I. (Faculty of Agriculture, University of Malaya, 1974)
A 3 x 3 factorial experiment involving 162 chicks was conducted to assess the performance and body composition of broiler chicks in response to varying protein levels (starter: 19, 22, 25 percent; grower: 17, 20, 23 percent) in combination with graded levels of cassava (0, 20, 40 percent). In general, protein and cassava levels in the diet gave little or no improvement in rate and efficiency of gain. With increasing levels of dietary protein, carcass protein was increased and carcass fat was decreased in a linear manner. Similarly, raising the cassava content up to 20 percent of the diet exerted a greater effect in increasing the protein and lowering the fat content of the carcas when supplemented up to 20 percent level, but further increases gave an inconsistent pattern of carcass composition